A DPS-PLL based rotor position estimation method for permanent magnet wind turbine. (November 2021) - Yu, Linxin; Wang, Dazhi; Liu, Zhen; Zheng, Di; Li, Wenhui
Abstract: Aiming at the problem of slow response and low tracking accuracy in the synchronous reference frame phase-locked loop (SRF-PLL) estimation of the permanent magnet synchronous generator (PMSG) rotor position when the wind speed changes suddenly, a rotor position estimation method based on the discrete position set phase-locked loop(DPS-PLL) is proposed. The estimated position in certain moment is selected from a discretized alternative position set. Then, combined with sliding mode observer, rotor position is obtained by calculating back-EMF cost function. The experimental results demonstrate the rotor position and speed can be detected accurately under sudden change of wind speed. The convergence time of estimation is within 42 ms. The estimated error of rotor position is less than 0.03 rad. The results show that the proposed method provides a satisfactory dynamic performance and strong disturbance rejection ability.